نمذجة العلاقة بين حجم الانفاق العام و مؤشر التنويع الاقتصادي في الجزائر - عبدلي، حنان; بوخاري ،بولرباح (جامعة الوادي University of Eloued, 2025)
This study aims at trying to model the relationship between the economic diversification index and the volume Many results have been .of government spending in Algeria for the period from 1990 to 2022 using VAR models reached in this research, most notably, there is a relationship of mutual influence between the diversification index and the volume of expenditures. The policy of expanding the volume of expenditures reduces the economic diversification index. However, the increase in the value of the index will lead to a very large increase in the volume of expenditures.
مقال
Keywords: دوال الاستجابة; دوال تحليل التباين; حجم النفقات الحكومية; مؤشر هيرشمان للتنويع الاقتصادي; Hirschman index of economic diversification; the size of government expenditures; var models